Percutaneous parametrial dose escalation in women with advanced cervical cancer: feasibility and efficacy in relation to long-term quality of life - Akbaba, Sati; Oelmann-Avendano, Jan Tobias; Bostel, Tilman; Rief, Harald; Nicolay, Nils; Debus, Jürgen; Lindel, Katja; Förster, Robert (Radiology and oncology, 2018)
Abstract Background We analyzed long-term quality of life (QoL) and prognostic factors for QoL as well as clinical outcome in patients with advanced cervical cancer (ACC) treated with primary radiochemotherapy (RChT) consisting of external beam radiotherapy (EBRT) with or without sequential or simultaneous integrated boost (SIB) to the parametria, intracavitary brachytherapy and concomitant chemotherapy (ChT). Patients and methods Eighty-three women were treated with primary RChT between 2008 and 2014. Survival of all patients was calculated and prognostic factors for survival were assessed in univariate and multivariate analysis. In 31 patients QoL was assessed in median 3 years (range 2-8 years) after treatment. QoL was compared to published normative data and the influence of age, tumour stage, treatment and observed acute toxicities was analyzed. Results Thirty-six patients (43.4%) died, 18 (21.7%) had a local recurrence and 24 (28.9%) had a distant progression. Parametrial boost (p = 0.027) and ChT (p = 0.041) were independent prognostic factors for overall survival in multivariate analysis. Specifically, a parametrial equivalent doses in 2-Gy fractions (EQD2) > 50 Gy was associated with an improved overall survival (OS) (p = 0.020), but an EQD2 > 53 Gy did not further improve OS (p = 0.194). Tumour size was the only independent prognostic factor for local control (p = 0.034). Lymph node status (p = 0.038) and distant metastases other than in paraaortic lymph nodes (p = 0.002) were independent prognostic factors for distant progressionfree survival. QoL was generally inferior to the reference population. Age only correlated with menopausal symptoms (p = 0.003). The degree of acute gastrointestinal (p = 0.038) and genitourinary (p = 0.041) toxicities correlated with the extent of chronic symptom experience. Sexual/vaginal functioning was reduced in patients with larger tumours (p = 0.012). Parametrial EQD2 > 53 Gy correlated with reduced sexual/vaginal functioning (p = 0.009) and increased sexual worry (p = 0.009). Whether parametrial dose escalation was achieved by sequential boost or SIB, did not affect survival or QoL. Conclusions Primary RChT is an effective treatment, but long-term QoL is reduced. The degree of acute side effects of RChT correlates with the extent of chronic symptoms. Patients benefit from parametrial SIB or sequential boost, but an EQD2 > 53 Gy does not further improve survival and negatively affects QoL.
Gesehen am 29.04.2020